(untitled) (Medicine Today, 2017)
One of the leading causes of blindness is corneal disorder. By keratoplasty we can restore vision of those patients to some extent and many surgeons are performing keratoplasty on vascularised cornea. Present study was done to evaluate its outcome. Patients (5-70 yrs) were recruited from eye ward of Dhaka Medical College Hospital from January, 2007 to December, 2007. Patients were selected on some criteria. Total 33 cases were evaluated before and after operation. This study was carried out to know pattern of blindness and to obtain the causes of corneal vascularisation and results of keratoplasty on these patients. Among 2 types of grafting all our patients were undergone penetrating keratoplasty. Male predominance (57.50) was marked as male are more prone to corneal diseases and trauma. Considering age group nobody is immune from corneal disease but children and young persons are more vulnerable. Socio-economic status of our maximum patients are middle-class or poor class. We got a rough idea about the causes leading to vascularisation of cornea. Amongst them; trauma, corneal ulcer, chemical injury and under nutrition are noted in our study. Out of 33 healthy grafts, visual improvement occurred in 24 cases. Visual results of grafting on vascularised corneas are variable. Our study concludes that trauma and corneal ulcer are the leading causes of corneal opacity which need penetrating keratoplasty. Whatever the cause of corneal vascularisation, prognosis of keratoplasty on such cases is not disappointing. Rather keratoplasty done on early notified corneal opacity with superficial vascularisation gives satisfactory results. Medicine Today 2017 Vol.29(1): 23-25